Role of Parts of Speech in Utterance Length for Mandarin-Speaking Children Aged 3–6 Years - Wu, Shang-Yu; Lin, Hung-Ching (SAGE open, 2024)
We investigated the effect of part of speech adoption on the utterance length of Mandarin-speaking children. A total of 209 typically developing Taiwanese children aged 3–6 years participated in the study. They included 90 boys and 119 girls recruited from preschools in Miaoli City, New Taipei City, and Taipei City. We collected children’s language samples in four contexts: conversation (school life), story retelling (“Little Red Riding Hood”), free play, and conversation (daily life). One-on-one conversation with participants comprised the main interaction form. Language samples collected from the participants were transcribed and analyzed; all words in the samples were coded with part of speech tagging. Part of speech factors that could predict utterance length were examined using stepwise regression. The results showed that prepositions and conjunctions had positive effects on utterance length while interjections had a negative effect. Increasing utterance length may be a teaching or clinical intervention goal for some children. Educators and clinicians can consider guiding such children to use prepositions and conjunctions to increase their utterance length. Plain language summary Role of parts of speech in utterance length for Mandarin-speaking children aged 3–6 years We investigated the effect of part of speech adoption on the utterance length of Mandarin-speaking children. A total of 209 typically developing Taiwanese children aged 3–6 years participated in the study. They included 90 boys and 119 girls recruited from preschools in Miaoli City, New Taipei City, and Taipei City. Language samples collected from the participants were transcribed and analyzed; all words in the samples were coded with part of speech tagging. Part of speech factors that could predict utterance length were examined using stepwise regression. The results showed that prepositions and conjunctions had positive effects on utterance length while interjections had a negative effect. Increasing utterance length may be a teaching or clinical intervention goal for some children. Educators and clinicians can consider guiding such children to use prepositions and conjunctions to increase their utterance length.